(x+12)(x+5)=(x-8)(x+7)-10

Simple and best practice solution for (x+12)(x+5)=(x-8)(x+7)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+12)(x+5)=(x-8)(x+7)-10 equation:


Simplifying
(x + 12)(x + 5) = (x + -8)(x + 7) + -10

Reorder the terms:
(12 + x)(x + 5) = (x + -8)(x + 7) + -10

Reorder the terms:
(12 + x)(5 + x) = (x + -8)(x + 7) + -10

Multiply (12 + x) * (5 + x)
(12(5 + x) + x(5 + x)) = (x + -8)(x + 7) + -10
((5 * 12 + x * 12) + x(5 + x)) = (x + -8)(x + 7) + -10
((60 + 12x) + x(5 + x)) = (x + -8)(x + 7) + -10
(60 + 12x + (5 * x + x * x)) = (x + -8)(x + 7) + -10
(60 + 12x + (5x + x2)) = (x + -8)(x + 7) + -10

Combine like terms: 12x + 5x = 17x
(60 + 17x + x2) = (x + -8)(x + 7) + -10

Reorder the terms:
60 + 17x + x2 = (-8 + x)(x + 7) + -10

Reorder the terms:
60 + 17x + x2 = (-8 + x)(7 + x) + -10

Multiply (-8 + x) * (7 + x)
60 + 17x + x2 = (-8(7 + x) + x(7 + x)) + -10
60 + 17x + x2 = ((7 * -8 + x * -8) + x(7 + x)) + -10
60 + 17x + x2 = ((-56 + -8x) + x(7 + x)) + -10
60 + 17x + x2 = (-56 + -8x + (7 * x + x * x)) + -10
60 + 17x + x2 = (-56 + -8x + (7x + x2)) + -10

Combine like terms: -8x + 7x = -1x
60 + 17x + x2 = (-56 + -1x + x2) + -10

Reorder the terms:
60 + 17x + x2 = -56 + -10 + -1x + x2

Combine like terms: -56 + -10 = -66
60 + 17x + x2 = -66 + -1x + x2

Add '-1x2' to each side of the equation.
60 + 17x + x2 + -1x2 = -66 + -1x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
60 + 17x + 0 = -66 + -1x + x2 + -1x2
60 + 17x = -66 + -1x + x2 + -1x2

Combine like terms: x2 + -1x2 = 0
60 + 17x = -66 + -1x + 0
60 + 17x = -66 + -1x

Solving
60 + 17x = -66 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
60 + 17x + x = -66 + -1x + x

Combine like terms: 17x + x = 18x
60 + 18x = -66 + -1x + x

Combine like terms: -1x + x = 0
60 + 18x = -66 + 0
60 + 18x = -66

Add '-60' to each side of the equation.
60 + -60 + 18x = -66 + -60

Combine like terms: 60 + -60 = 0
0 + 18x = -66 + -60
18x = -66 + -60

Combine like terms: -66 + -60 = -126
18x = -126

Divide each side by '18'.
x = -7

Simplifying
x = -7

See similar equations:

| 1+3(6-6)+8= | | (x+5)(5-x)=(12+x)(4-x)+1 | | -20+6q=2 | | 12=20+2p | | 5x+3x-3y+4y= | | 24ab-2a+3-4ab= | | 3(2a+1)=11+4a | | 3(x-5)+2(x+1)=2 | | x^2+5-16=0 | | 3(x+1)=5x+7 | | x(x+2)=360 | | x+x^2=100 | | (x+y)(x^2-12xy-y^2)= | | 2+12x=122+x | | 3x^3-8x^2-60x=0 | | 2x+6=4-3x | | 4w^2-60w+200=400 | | 3ln(x)-ln(2)=4 | | 4w^2-60w+200=0 | | (x+1)(4x-3)=0 | | df=14 | | 3(z-2)=27 | | (q-5)x^2-4x-q=0 | | 4w^2-80w+400=200 | | 6ln(x+8)-2ln(x)= | | x^5=-25 | | 4w^2-100w+200=0 | | 6x-2x=21-141 | | 4w-100w+200=0 | | 4w-100+200=0 | | 3n-33n+90=0 | | y^2-10y-4x+33=0 |

Equations solver categories